2017
DOI: 10.1007/s11356-017-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests

Abstract: The stored grain insects cause great damage to grains under storage conditions. Synthetic insecticides and fumigants are considered as key measures to control these stored grain insect pests. However, the major issue with these chemicals is grain contamination with chemical residues and development of resistance by insect pests to these chemicals. Biological control is considered as a potential alternative to chemical control especially with the use of pathogens, alone or in combination with selective insectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…These results were consistent with the studies reported by Athanassiou et al, in which a six-fold increase in adult mortality of T. confusum was observed when treated with B. bassiana and DE, compared with either B. bassiana or DE alone [15]. Similarly, Ashraf et al clearly indicated that M. anisopliae combined with DE or thiamethoxam had a synergistic effect, compared to their individual efficacies, and was more effective in controlling four stored insect pests [35]. Likewise, Wakil et al found that B. bassiana combined with DE or the neonicotinoid insecticide thiamethoxam increased the mortality of R. dominica adults, compared with individual treatments, and a significant additive effect was observed [32].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results were consistent with the studies reported by Athanassiou et al, in which a six-fold increase in adult mortality of T. confusum was observed when treated with B. bassiana and DE, compared with either B. bassiana or DE alone [15]. Similarly, Ashraf et al clearly indicated that M. anisopliae combined with DE or thiamethoxam had a synergistic effect, compared to their individual efficacies, and was more effective in controlling four stored insect pests [35]. Likewise, Wakil et al found that B. bassiana combined with DE or the neonicotinoid insecticide thiamethoxam increased the mortality of R. dominica adults, compared with individual treatments, and a significant additive effect was observed [32].…”
Section: Discussionsupporting
confidence: 91%
“…However, there have been few reports on its use in the control of agricultural pests. Our results showed that DE has a certain control effect on the invasive insect WFT, which is similar to its control effect against invasive red fire ants, whose efficacy was lower than stored grain insect pests [32,35,37,38]. The differences in control effects were due to the fact that some insects are more sensitive to DE, due to their anatomical and physiological characteristics, and may also be related to differences in the cuticular composition of different insect species [34,37].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations